Features of impact between Eastern and Western Literature - Mohd. Shamsuddin, Salahuddin; Ahmad, Siti Sara bint Hj. (Advances in Social Sciences Research Journal, 2020)
No doubt that modern Arab literature has been influenced by Western literature more than it was influenced by ancient Arabic literature, whether by the missionaries, occupiers, merchants, and investors who arrived at Arab countries or by the scientific missions sent by Arab countries to European capitals or by Arab immigrants to the West. This influence was either through the translation, or through reading in the original languages ​​of Western literature, and this second method was more influential in modern Arabic literature, because translation loses many of the characteristics of artistic literatures that have a close connection with the language.. We mentioned in this research the link between East and West, and between Arab literature and European literature, and the features of impact between them through the process of transferring the literary heritage from East to West through several crossings, and its study to extract the literary and cultural treasures through the efforts of missionaries from Orientalists that were the first nucleus of modern Western civilization. We also dealt with the features of renewal in Arabic literature, Arabic poetry and its schools in the modern era. We focused on the Divan school, the Apollo school and Diaspora School, especially the nature of poetry and truth of free modern realist poetry. We also mentioned the high demand for translated eastern literature in European countries, and its inclusion by the writers, poets and writers in their literary writings. We used the descriptive approach that is always suitable for such literary and critical topics.